Design and Kinematic Analysis of Mechanized Rice Transplanting Mechanism - Khan, Liaquat Ali; Khan, M Kamran; Kaleem, M Mubashir; Rehman, Muqtasid; Nasir, Wahaj; Liaquat, Huzaifa (European Journal of Applied Sciences, 2025)
Precise pick and place point of rice transplanting arm is necessary for the efficient production of rice. Literature shows that inaccurate picking and placing points reduces the rice production efficiency by almost 20-30%. This study is made to obtain the path of rice transplanting arm using linkage, determined the path mathematically and designed cam and follower to simulate it. Pump type rice transplanting arms have the problem of links size adjustment, if link lengths are not selected properly, the points of interest are disturbed, hence lowering the efficiency. A detailed kinematic analysis of link lengths, position of coupler points and verification via Grashoff conditions is made in this research, the results of different link lengths with their effect on path of transplanting arm is done, and the best of them is selected and further analyzed. Finally, the pump type transplanting arm is designed, simulated, and tested for different crank angles, position, velocity and acceleration analysis is done. Results from mathematical model and simulation are compared. Two arms-based rice transplanters have been designed, and a prototype is made and tested. The results are close to design parameters.